Recent Progress in Chiral Topological Quantum Interface - Jiang, Ping; Ma, Na; Qiao, Xiaozhen; Zhang, Hui (Frontiers in Physics, 2022)
Chiral quantum optics and Topological photonics are both emerging field of research, which have attracted great attention in recent years. Chiral quantum optics provides a new approach to achieve full quantum control of light-matter interaction in a novel manner, which has potential possibilities for the implementation of complex quantum information networks. Meanwhile, topological photonics provides a novel route for designing and realizing optical devices with unprecedented functionalities, such as robust light propagation, the immunity to various structural imperfections, back-scattering suppression as well as unidirectional transmission. The application of topological photonics in chiral quantum optics will promote the whole performance of integrated quantum devices with topological protection. In this review, we summarize the progress of chiral quantum optics and topological photonics firstly. Then, we mainly focus on the research of topological chiral edge states based on photonic quantum spin-Hall effect and photonic quantum valley-Hall effect. Furthermore, we introduce the recent work of chiral topological quantum interfaces formed by embedding quantum dots into the interface between two topologically distinct photonic crystal structures. At last, we give a short outlook on the future development direction and prospects for application of topological chiral quantum interfaces.